A clinical update on vaccines: focus on determinants of under-immunization and special considerations for adolescents. Issue 2 (April 2020) - Brodie, Nicola; Metzenberg, Gretchen E.; Silberholz, Elizabeth A.
Abstract : Purpose of review: The current article reviews recent literature related to pediatric and adolescent vaccination, specifically focusing on social determinants of under-immunization, expanding adolescent immunization rates, and new recommendations surrounding the meningococcal serotype B vaccine (MenB). Recent findings: Vaccine refusals and vaccine-preventable diseases have been rising in some parts of the world, and appear to be linked to household factors, such as a family's socioeconomic status. Adolescents have lower immunization rates than younger children. Newer vaccines targeted at adolescents, such as the MenB vaccine, have yet to be widely accepted by pediatric providers, parents, and patients. Summary: Pediatric healthcare providers should attempt to increase local immunization rates by vaccinating children at all eligible office visits and utilizing electronic health record decision-support tools. Although the number of families who choose not to vaccinate their children may be rising, providers can be innovative (e.g. incorporate digital vaccine reminder systems) and increase their familiarity with new vaccine recommendations to continue to prevent serious vaccine-preventable diseases.